Representation of prefrontal axonal efferents in the thalamic nucleus reuniens in a rodent model of fetal alcohol exposure during third trimester - Smith, Eva A.; Gursky, Zachary H.; Klintsova, Anna Y. (Frontiers in Behavioral Neuroscience, 2022)
Alcohol exposure (AE) during the prenatal period could result in fetal alcohol spectrum disorders (FASDs), one of many deficits of which is impaired executive functioning (EF). EF relies on the coordination of activity between the medial prefrontal cortex (mPFC) and hippocampus (HPC) by the thalamic nucleus reuniens (Re), a structure that has been shown to be damaged following high-dose AE in a rodent model of third trimester exposure. Notably, mPFC neurons do not project directly to HPC, but rather communicate with it via a disynaptic pathway where the first cortical axons synapse on neurons in Re, which in turn send axons to make contacts with hippocampal cells. This experiment investigated the effect of binge AE (5.25 g/kg/day, two doses 2 hours apart) during postnatal days 4-9 on the length of medial prefrontal axonal projections within Re in Long Evans rat. AE reduced the cumulative length of mPFC-originating axon terminals in Re in female rats, with male rats exhibiting shorter cumulative lengths when compared to female procedural control animals. Additionally, Re volume was decreased in AE animals, a finding that reproduced previously reported data. This experiment helps us better understand how early life AE affects prefrontal-thalamic-hippocampal connectivity that could underlie subsequent EF deficits.